2022
DOI: 10.1111/jipb.13249
|View full text |Cite
|
Sign up to set email alerts
|

OsMAPK6 phosphorylates a zinc finger protein OsLIC to promote downstream OsWRKY30 for rice resistance to bacterial blight and leaf streak

Abstract: Rice OsLIC encoding a CCCH zinc finger transcription factor plays an important role in immunity. However, the immune signaling pathways that OsLIC‐involved and the underlying mechanisms that OsLIC‐conferred resistance against pathogens are largely unclear. Here, we show that OsLIC, as a substrate for OsMAPK6, negatively regulates resistance to Xanthomonas oryzae pv. oryzae (Xoo) and X. oryzae pv. oryzicola (Xoc) by directly suppressing OsWRKY30 transcription. Biochemical assays showed that OsLIC bound to OsWRK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…MdBBX7/MdCOL9 can be directly ubiquitinated and degraded by E3 ubiquitin ligase MIEL1, which reduces apple tolerance to drought stress [ 37 ]. CCCH-type zinc finger protein OsLIC, as a substrate of OsMAPK6, can be activated by phosphorylation of OsMAPK6 to regulate rice resistance to Xoo and Xoc [ 38 ]. AtZAT6 positively modulates expression levels of stress-related genes by directly binding to the promoter region of pathogen-related genes like PR1 and PR5 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…MdBBX7/MdCOL9 can be directly ubiquitinated and degraded by E3 ubiquitin ligase MIEL1, which reduces apple tolerance to drought stress [ 37 ]. CCCH-type zinc finger protein OsLIC, as a substrate of OsMAPK6, can be activated by phosphorylation of OsMAPK6 to regulate rice resistance to Xoo and Xoc [ 38 ]. AtZAT6 positively modulates expression levels of stress-related genes by directly binding to the promoter region of pathogen-related genes like PR1 and PR5 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rice, phosphorylation of OsWRKY31 by OsMPK3, OsMPK4, and OsMPK6 enhances resistance to Magnaporthe oryzae (S. Wang et al ., 2023). OsMAPK6 phosphorylates a zinc finger protein OsLIC to promote downstream OsWRKY30 resistance to bacterial blight and leaf streak (L. H. Wang et al ., 2022). BBXs through post‐translational modifications to mediate plant stress responses have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs in other fungi such as Aspergillus fumigatus and Torrubiella hemipterigena are annotated as CCCH zinc finger DNA binding proteins. Although CCCH zinc finger proteins were known as RNA-binding proteins ( Fu and Blackshear, 2017 ), Recent studies showed that CCCH zinc finger proteins also bind to DNA and modulate transcription ( Zou et al, 2018 ; Wang et al, 2022 ). Therefore, we speculate that FoDbp40 may have the ability to bind target DNA and function in transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…CCCH zinc finger proteins are known as RNA-binding proteins and associated with post-transcriptional regulation of mRNA ( Fu and Blackshear, 2017 ). In addition to its role in RNA metabolism, recent studies demonstrated that CCCH zinc finger proteins also modulate transcription ( Zou et al, 2018 ; Wang et al, 2022 ). A RNA-binding CCCH zinc finger protein Zc3h10 was also proved to activate UCP1 promoter by binding to a distal upstream region ( Yi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%